Management of medullary thyroid cancer based on variation of carcinoembryonic antigen and calcitonin - Wang, Bo; Huang, Jie; Chen, Li (Frontiers in Endocrinology, 2024)
Carcinoembryonic antigen (CEA) and calcitonin (Ctn) are pivotal biomarkers in the diagnosis and management of medullary thyroid carcinoma (MTC). However, their diagnostic reliability in perioperative period remains a topic of ongoing debate. This review synthesizes researches on perioperative fluctuations in CEA and Ctn levels, and evaluates the impact of their different combinations on MTC diagnosis, treatment decisions, and prognosis. Our findings highlight it is crucial to understand and interpret the various combinations of CEA and Ctn fluctuations within a clinical context. Furthermore, to reduce diagnostic errors and improve patient outcomes, we recommend follow-up diagnostic and treatment protocols designed to address the potential pitfalls associated with the use of these biomarkers.